Timor-Leste Trade Facilitation Challenges for Women Traders and Freight Forwarders : Survey Findings and Recommendations - World Bank (World Bank, Washington, DC, 2021)
Trade is widely recognized to be an engine of growth that creates jobs, reduces poverty, and increases economic opportunity. Trade facilitation measures are non-discriminatory and apply to all traders in their design; however, these measures may not necessarily impact or benefit all traders in similar ways. There is a global lack of data on how trade facilitation interventions impact traders by gender at the firm level. There is also a global vacuum of knowledge of the exact proportion of cross-border traders that are women. Few countries, if any, can easily confirm the number of women that undertake cross-border trade in their respective countries. This note presents findings of the survey work in Timor-Leste. Timor-Leste is a small island country within the Malay Archi-pelago. It includes the enclave of Oecussi-Ambeno, situated on the Western (Indonesian) part of the island and the islands of Atauro and Jaco. There are ports on Oecusse and Atauro Island that provide domestic ferry traffic, and Dili Port operates as the only international port for Timor-Leste. Indonesia is Timor-Leste’s biggest trading partner.